Translation as Allegory: Adaptation of Premchandâ€™s â€œShatranj Ke Khilariâ€ into Film - Singh, Govt. P.G. College, Dausa, Rajasthan, India, Omendra Kumar (Asiatic: IIUM Journal of English Language and Literature, 2014)
Roman Jakobson's idea that adaptation is a kind of translation has been further expanded by functionalist theorists who claim that translation necessarily involves interpretation. Premised on this view, the present paper argues that the adaptation of Premchand's short story â€œShatranj ke Khilariâ€ into film of that name by Satyajit Ray is an allegorical interpretation. The idea of allegorical interpretation is based on that ultimate four-fold schema of interpretation which Dante suggests to his friend, Can Grande della Scala, for interpretation of his poem Divine Comedy. This interpretive scheme is suitable for interpreting contemporary reality with a little modification. As Walter Benjamin believes that a translation issues from the original â€“ not so much from its life as from its after-life â€“ it is argued here that in Satyajit Ray's adaptation Premchand's short story undergoes a living renewal and becomes a purposeful manifestation of its essence. The film not only depicts the social and political condition of Awadh during the reign of Wajid Ali Shah but also opens space for engaging with the contemporary political reality of India in 1977.